2018
DOI: 10.3892/ol.2018.8505
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cell proliferation is suppressed by microRNA‑3160‑5p via targeting of F‑box and WD repeat domain containing 8

Abstract: Abstract. MicroRNAs (miRNAs/miRs), which are endogenous non-coding single-stranded RNAs 19-25 nucleotides in length, regulate gene expression by blocking translation or transcription repression. The present study revealed that miR-3160-5p was widely expressed in prostate cancer cells by reverse transcription-quantitative polymerase chain reaction. There was a negative association between the expression of miR-3160-5p and F-box and WD repeat domain containing 8 (Fbxw8) in prostate cancer DU145 cells. A lucifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Studies have shown that Fbxw8 is involved in cancer cell growth via proteolysis 89 . Consistent with the finding that CUL7 participates in the promotion of migration and invasion in choriocarcinoma cells 55 , Fbxw8 expression levels are increased in human trophoblast cell lines, including choriocarcinoma 90 , and regulate cell proliferation 23 , 89 91 (Fig. 2 ), while the effect of Fbxw8 on the tumor migration, invasion, and metastasis remains unclear, indicating that more research about the impact of Fbxw8 on cancer progression is needed.…”
Section: The Ring Box Protein Rbx1 Adaptor Skp1 and F-box Proteins supporting
confidence: 71%
See 1 more Smart Citation
“…Studies have shown that Fbxw8 is involved in cancer cell growth via proteolysis 89 . Consistent with the finding that CUL7 participates in the promotion of migration and invasion in choriocarcinoma cells 55 , Fbxw8 expression levels are increased in human trophoblast cell lines, including choriocarcinoma 90 , and regulate cell proliferation 23 , 89 91 (Fig. 2 ), while the effect of Fbxw8 on the tumor migration, invasion, and metastasis remains unclear, indicating that more research about the impact of Fbxw8 on cancer progression is needed.…”
Section: The Ring Box Protein Rbx1 Adaptor Skp1 and F-box Proteins supporting
confidence: 71%
“…Numerous studies have demonstrated that miRNAs also contribute to the initiation and development of various human cancers 126 , 127 . miR-218 may be an effective therapeutic target for human choriocarcinoma cell growth 128 and miR-3160-5p suppressed the proliferation of DU145 prostate cancer cells and was negatively related to the expression of Fbxw8 91 . For Fbxw11, miR-106b-25, and miR-182 regulated the cell proliferation, migration, and invasion in NSCLC by targeting Fbxw11 96 , 97 .…”
Section: Cul7 Substrate Proteins In Development and Cancermentioning
confidence: 99%
“…Hsa_circ_0003970 and hsa_circ_0005848 interacted with miRNA-204-5p, which is a tumor suppressor that promotes apoptosis by targeting BCL2 in PCa cells ( Lin et al, 2017 ). Hsa_circ_0005848 and hsa_circ_0006754 related miR-3160-5p is a PCa cell proliferation suppressor that targets the F-box protein ( Lin et al, 2018 ). MiR-548 acts as an anti-oncogenic factor that inhibits the phosphoinositide three-kinase (PI3K)/AKT signaling pathway in lung cancer and is associated with high-risk Gleason scores in PCa ( Shi et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…FBXW8 promotes proliferation of colon carcinoma through directing the proteasomal degradation of cyclin D1 during S phase [33]. Thus, FBXW8 regulates multiple cell cycle regulators to promote cancer; however, several miRNAs were found to be involved in restricting the expression level of FBXW8 in cancer [53,54]. In contrast to oncogenic role, FBXW8 also acts as tumor suppressor through promoting degradation of IRS‐1 [55].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that FBXW8 is involved in promoting many cancers including choriocarcinoma, prostate, pancreatic, and colon cancer [33,52,53]. In choriocarcinoma, FBXW8 promotes malignancy through controlling the expression levels of CDK1, CDK2, cyclin A, cyclin B, and p27 [52].…”
Section: Discussionmentioning
confidence: 99%